The Effectiveness of Picture Series as a Media to Improve Students' Writing Skill - Yayi Wahyu Ilmillahdini; Puji Sumarsono (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2014)
The Effectiveness of Picture Series as a Media to Improve Students' Writing Skill